Pengaruh Etos Kerja, Disiplin Kerja, Dan Lingkungan Kerja Terhadap Kinerja ASN - Arnando, Anjas Putra; Syarif, M. Amirudin (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
The purpose of this study was to determine the effect of work ethic, work discipline, and work environment on the performance of ASN South Sumatra Province, where the number of samples in this study were 71 respondents using questionnaire data collection techniques, with Likert scale measurements. This research is quantitative using validity, reliability, classical assumption test, multiple liner regression using SPSS 25. Where in this study Work Ethic, Work Discipline and Work Environment have a personal influence on the ASN Performance of the Supreme Audit Agency of South Sumatra Province. Based on the results of research and discussion regarding the effects of work ethic, work discipline, and work environment on ASN performance at the South Sumatra Provincial Audit Board, it is found that work ethic has a positive and significant effect on ASN performance at the South Sumatra Provincial Audit Board, Work Discipline has a positive and significant impact on the performance of ASN at the South Sumatra Reduction Permerriksa Agency, Work Environment has a positive and significant impact on the performance of ASN at the South Sumatra Reduction Permerriksa Agency, Work Ethos, Work Discipline and Work Environment have a joint impact on the performance of ASN at the Serlatan Surmaterra Reduction Permerriksa Agency.